Human soluble ACE2 improves the effect of remdesivir in SARS‐CoV‐2 infection - Vanessa Monteil; Matheus Dyczynski; Volker M Lauschke; Hyesoo Kwon; Gerald Wirnsberger; Sonia Youhanna; Haibo Zhang; Arthur S Slutsky; Carmen Hurtado del Pozo; Moritz Horn; Nuria Montserrat; Josef M Penninger; et al. (EMBO Molecular Medicine)
Abstract There is a critical need for safe and effective drugs for COVID‐19. Only remdesivir has received authorization for COVID‐19 and has been shown to improve outcomes but not decrease mortality. However, the dose of remdesivir is limited by hepatic and kidney toxicity. ACE2 is the critical cell surface receptor for SARS‐CoV‐2. Here, we investigated additive effect of combination therapy using remdesivir with recombinant soluble ACE2 (high/low dose) on Vero E6 and kidney organoids, targeting two different modalities of SARS‐CoV‐2 life cycle: cell entry via its receptor ACE2 and intracellular viral RNA replication. This combination treatment markedly improved their therapeutic windows against SARS‐CoV‐2 in both models. By using single amino‐acid resolution screening in haploid ES cells, we report a singular critical pathway required for remdesivir toxicity, namely, Adenylate Kinase 2. The data provided here demonstrate that combining two therapeutic modalities with different targets, common strategy in HIV treatment, exhibit strong additive effects at sub‐toxic concentrations. Our data lay the groundwork for the study of combinatorial regimens in future COVID‐19 clinical trials.